Survey on wait-free consensus protocol in distributed systems. (3rd January 2023) - Rani, Radha; Mahato, Dharmendra Prasad
Computer applications are transitioning from centralised to decentralised automation in the modern industrial era. The consensus algorithm is a critical component in decentralised applications. Wait-free consensus is an unresolved issue in asynchronous systems. Deterministic protocols are known to be incapable of solving the wait-free consensus problem. Wait-free consensus protocol implementation occurs when all processors complete their predefined steps regardless of the execution speed of the other processors. Many randomised algorithms for wait-free consensus have been proposed, but no deterministic algorithm is possible. In this paper, we present a survey of wait-free consensus algorithms that have been studied and are currently being used in some well-known applications. There is also discussion of open issues and challenges in deploying various consensus mechanisms. This survey will provide a detailed understanding of the wait-free consensus protocol and will aid in the direction of research in the field of designing consensus algorithms.